Board Games Revisited w/ Dr. Kerri Evans, Dr. Keisha Allen, Netty Lichtman, Brittany Murillo, & Kaylee Reyes - Anson, Ian; Evans, Kerri; Allen, Keisha; Murillo, Brittany; Evans, Kaylee; Lichtman, Netty (UMBC Center for Social Science Research, 2023)
On this episode we return to our discussion of pedagogical simulations and the immigrant experience in educational settings from Dr. Kerri Evans, Assistant Professor of Social Work at UMBC; Dr. Keisha Allen, formerly of UMBC, who is now Assistant Professor in the School of Education at the University of Maryland, College Park; recent UMBC graduates Brittany Murillo and Kaylee Evans; and current UMBC senior, Netty Lichtman.